(untitled) (Experimental biology, 2023)
The article presents data on the assessment of the adaptive qualities of sturgeon fry according to the reactions of the central nervous system using the "open field" test. This test makes it possible to assess the severity and dynamics of elementary behavioral acts in fish under stressful conditions. The test was carried out both individually and in a group of several individuals. The most acceptable option turned out to be a group of five individuals of any sturgeon species, since video analysis is easy to perform and the number of individuals makes it possible to shorten the series of experiments. The obtained data on the assessment of the adaptive qualities of juveniles according to the reactions of the central nervous system as a whole show that sterlet juveniles have high mobility and an acute reaction to such stimuli as bright light and high-frequency sound, beluga and Russian sturgeon juveniles have a sharp reaction to low- and high-frequency sounds. All of the above positively characterizes the fingerlings intended for stocking natural water bodies. The proven methods for assessing the quality of released fry are easily applicable in the conditions of sturgeon fish farms and are recommended for use at a sturgeon hatchery, since it is possible to evaluate the entire batch of stocked fish from a sample.